2019
DOI: 10.1038/s41598-019-44022-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning Approach for the Development of a Novel Predictive Model for the Diagnosis of Hepatocellular Carcinoma

Abstract: Because of its multifactorial nature, predicting the presence of cancer using a single biomarker is difficult. We aimed to establish a novel machine-learning model for predicting hepatocellular carcinoma (HCC) using real-world data obtained during clinical practice. To establish a predictive model, we developed a machine-learning framework which developed optimized classifiers and their respective hyperparameter, depending on the nature of the data, using a grid-search method. We applied the current framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 39 publications
0
56
0
2
Order By: Relevance
“…Our data also indicated that obesity was a major risk factor for the development of T2DM 43 . The previous studies have demonstrated the significant role of boosting method in other medical fields, such as urinary tract infections 44 , hepatocellular carcinoma diagnosis 45 , prediction of hip fracture 46 . Our results confirmed the outstanding performance of the boosting method in the risk assessment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also indicated that obesity was a major risk factor for the development of T2DM 43 . The previous studies have demonstrated the significant role of boosting method in other medical fields, such as urinary tract infections 44 , hepatocellular carcinoma diagnosis 45 , prediction of hip fracture 46 . Our results confirmed the outstanding performance of the boosting method in the risk assessment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgery, transcatheter arterial chemoembolization (TACE), radiofrequency ablation, radiotherapy and other therapeutic approaches can control the progress of HCC, generally speaking, HCC is still under exploration in the areas of molecular typing, molecular diagnosis and gene target selection. Although CDH 21 , LDH 22 , NCOR1 23 and other mutant genes are new biomarkers in HCC subtype classification 24,25 , identification of gene mutations that affect recurrence is complex but will have clinical significance. Meanwhile, various probability theories and linear algebra algorithms can be used for comprehensive analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning has recently become utilized in the field of medicine (5,18), including for the detection of hepatocellular carcinoma (19), the prediction of urinary tract infections in the emergency department (20), the prediction of hip fractures (21), the diagnosis of diabetic retinopathy (22), and the prediction of heart failure (23). Machine learning is also applied in the field of neurotology where it has been evaluated for use as a new diagnostic posturographic tool for disorders of stance, with an overall sensitivity and specificity of about 0.9 (8).…”
Section: Discussionmentioning
confidence: 99%